Optimization of biodegradable sago-based film formulation for food packaging - Md. Wahi, Nurhazerin (2016)
Millions of tons of food plastic packaging have been produced and deposited for decades. These types of plastics are made of petroleum-based materials and they are called synthetic plastics which are expensive, toxic, totally non-biodegradable and may contribute to environmental pollution. Great concerns regarding environmental issue has produced an alternative idea to replace the synthetic plastic with biodegradable plastics based on sago starch. This research focuses on the synthesis and characterization of biodegradable sago film formulation. In order to obtain the optimal conditions in developing the films, optimization process has been carried out. The sago film formulations were characterized using scanning electro n microscopy for the morphology study of film formulation. Fourier transform infrared spectroscopy had successfully shown the chemical structure and bonding while cinnamaldehyde had successfully inhibited E. coli bacteria growth by using agar diffusion method. A central composite design technique from response surface methodology was used to investigate the effects of independent variables on biodegradable sago film formulation properties. Biodegradable sago film formulation was analyzed for tensile strength (TS), elongation at break (EB), elastic modulus (EM) and water vapor permeability (WVP). The statistical analysis results show that the data appropriately fitted a second-order polynomial model where the coefficients of determination, R2 are 0.8192, 0.8451, 0.8036 and 0.8941 for TS, EB, EM and WVP respectively. The independent variables of linear sago/chitosan blend and quadratic cinnamaldehyde had significant effect on TS. The linear cinnamaldehyde and quadratic cinnamaldehyde and glycerol/sorbitol-plasticized had significant effect on EB. Meanwhile, EM was significantly affected by both linear sago/chitosan and cinnamaldehyde and quadratically by glycerol/sorbitol-plasticized. The WVP was significantly affected by both linear sago/chitosan and glycerol/sorbitol-plasticized. The results show that the best film formulations for sago film formulation within the experimental ranges are 16.36 wt.% sago/chitosan, 41.11 wt.% glycerol/sorbitol and 0.7350 wt.% cinnamaldehyde for 135.49 MPa of TS; 57.01 wt.% sago/chitosan, 59.14 wt.% glycerol/sorbitol and 0.6400 wt.% cinnamaldehyde for 0.6012% EB and 41.03 wt.% sago/chitosan, 30.32 wt.% glycerol/sorbitol and 0.8364 wt.% cinnamaldehyde for 8.45x106 MPa of EM. Furthermore, for the optimum composition of 1x10-7 g/Pa.s.m2 of WVP, the experimental values are 79.66 wt.% sago/chitosan, 83.64 wt.% glycerol/sorbitol and 0.5430 wt.% cinnamaldehyde. Finally, the present findings indicate that the biodegradable sago-based film can be a potential plastic packing with appropriate optimized formulation values.